Determinan Keberhasilan Revitalisasi Posyandu - Marianus Ketmoen; Pius Weraman; Muntasir Muntasir; Imelda Februati Ester Manurung; Sabina Gero (Journal of Telenursing (JOTING), 2022)
This study aims to determine the determinants of the success of posyandu revitalization, which are influenced by the activeness of posyandu cadres, education/training, incentives, infrastructure and community participation in the working area of ​​Nunpene Health Center and Bitefa Health Center, East Miomaffo District, TTU Regency. The type of research used is cross-sectional. The results showed that the tcount for the variables of cadre activity, education/training, incentives, infrastructure and community participation were 1,245, 1,202, 1,867, 6,996, and 13,406, respectively, with a significance value for each variable, namely 0.216, 0.232. , 0.065, 0.000, and 0.000. The fcount value obtained is 107,290 with a significance of 0.000. In conclusion, cadre activity, education/training, incentives, infrastructure, and community participation positively and significantly impact the revitalization of posyandu. Keywords: Cadre Activity, Posyandu Revitalization